Pengaruh E-Service Quality (SIMAK) Terhadap Kepuasan Layanan Mahasiswa Universitas Muhammadiyah Mamuju - Muslim, Bohari; Shaddiq, Syahrial (Journal of Management Branding, 2024)
This research is a type of descriptive research with a quantitative approach, where the sample size consists of 80 students of Universitas Muhammadiyah Mamuju. The results of the analysis and discussion show that the coefficient of determination or R Square, reaches 0.789 or equivalent to 78.9%, indicating that student satisfaction is influenced by E-Service Quality by 78.9%. The T test or partial test shows that E-Service Quality (X) has an effect of 0.750 with a significance of 0.000 <0.05. The calculated t value is 11.333> t table 1.66462, which indicates that E-Service Quality significantly affects student service satisfaction at Universitas Muhammadiyah Mamuju. The F test shows that E-Service Quality has a significance level of 0.000. This indicates that it is smaller than the alpha value of 0.05 (5%), meaning that E-Service Quality (SIMAK) has an influence on student satisfaction.